2018
DOI: 10.1038/s41557-018-0147-z
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibiting amyloid-β cytotoxicity through its interaction with the cell surface receptor LilrB2 by structure-based design

Abstract: Inhibiting the interaction between ß-amyloid (Aß) and a neuronal cell surface receptor, LilrB2, has been suggested as a potential route for treating Alzheimer’s disease (AD). Supporting this approach, AD-like symptoms are reduced in mouse models following genetic depletion of the LilrB2 homolog. In its pathogenic, oligomeric state, Aß binds to LilrB2, triggering a pathway to synaptic loss. Here we identified the LilrB2 binding moieties of Aß ( 16 KLVFFA 21 ) and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 45 publications
(71 reference statements)
9
54
0
Order By: Relevance
“…Therefore, binding between oAβ and PirB would recruit cofilin-signaling modules, which leads to actin depolymerization, resulting in synaptic dysfunction and cognitive deficits [93]. Compounds inhibiting Aβ/LilrB2 interactions in vitro have been identified, and potentially bioactive Aβ/LilrB2 inhibitors such as ALI6 can inhibit Aβ-mediated neurotoxicity in primary neurons [94].…”
Section: Lilrb2mentioning
confidence: 99%
“…Therefore, binding between oAβ and PirB would recruit cofilin-signaling modules, which leads to actin depolymerization, resulting in synaptic dysfunction and cognitive deficits [93]. Compounds inhibiting Aβ/LilrB2 interactions in vitro have been identified, and potentially bioactive Aβ/LilrB2 inhibitors such as ALI6 can inhibit Aβ-mediated neurotoxicity in primary neurons [94].…”
Section: Lilrb2mentioning
confidence: 99%
“…The binding ability, sites, and interactions between compound and target proteins were achieved and analyzed by classical molecular dynamics using AutoDockTools-1.5.6, Pymol 2.3 and Discovery Studio 4.5 Client [77,78]. The 3D chemical structural formulas of candidate compounds were obtained from PubChem and energy minimizing employed to ChemBioDraw 3D.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Therefore the LilrB2 binding moieties of Aβ with identified structure, be 16 KLVFFA 21 , has been used to inhibit this interaction and its efficacy has been studied in vivo and in vitro. This study showed that these inhibitors are potential therapeutic agents against AD (Cao et al, 2018).…”
Section: Alzheimer's Disease Treatment With Small Molecule β-Amyloid mentioning
confidence: 66%